Introduction, issue 85 - Fattouh, B (Oxford Institute for Energy Studies, 2011)
The accident at Japan’s Fukushima Daiichi nuclear complex earlier this year has reignited an old debate about the future role of nuclear power in the global energy mix. The repercussions of the Fukushima accident are likely to be felt for quite some time with some observers claiming that the accident has put an end to the ‘nuclear renaissance’. Malcolm Keay is of this view arguing that ‘although Fukushima may not have the traumatic impact of Three Mile Island or Chernobyl, it is likely to be another turning point on the winding road of nuclear development – renaissance postponed, at least for the foreseeable future.’ But not everyone agrees.